Laparoscopic pelvic organ prolapse repair by mesh interposition following radical cystectomy. Issue 3 (20th March 2019) - Abe, Hirokazu; Fan, Bo; Huang, Tingwen; Komori, Hiroka; Ochi, Atsuhiko; Suzuki, Koichiro; Kitagawa, Yasuhide; Shiga, Naoki
Abstract : Introduction: The present study aims to introduce laparoscopic treatment by the interposition of polypropylene mesh for a pelvic organ prolapse in females following radical cystectomy for treating muscle‐invasive bladder carcinoma. Case presentation: The patients included two women aged 77 and 79 years with symptomatic enterocele following radical cystectomy and ileal conduit urinary diversion. We performed laparoscopic sacrospinous colpopexy using polypropylene and polypropylene/ePTFE composite meshes. Conclusion: No recurrent prolapse occurred during 26 and 14 months of follow‐up after the operation. No severe perioperative complications were noted. This is a first report on cases of laparoscopic sacrospinous colpopexy for post‐cystectomy pelvic organ prolapse. Our procedure could be safely performed in two patients with post‐cystectomy pelvic organ prolapse.